Abnormal Grain Growth Mechanism in the Twin-Roller Cast Al-Fe-Si Alloy in the Annealing Process. (15th June 2020) - Zhu, Y. Z.; Peng, H.; Huang, H.; Li, J. C.
Abstract : The twin-roller casting process is a novel technology used to produce aluminium and other alloys. In this study, the Al-Fe-Si alloy was twin-roller cast into a billet with a thickness of 7.0 mm. This was followed by an annealing process at 480°C for 16 hours. Abnormal grains of more than 15 mm in the nominal diameter were found to have formed on the surface of the billet. Scanning electronic microscopy observation, energy diffraction spectrum, microarea X-ray diffraction, and electronic backscattered diffraction analysis were performed to study this abnormal grain growth. The results showed that abnormal grain nucleates in the region of (100) <001> texture formed in the twin-roller casting process. The growth of abnormal grain was governed by the coalescence of the abnormal grain with its surrounding normal grains, with an average orientation angle of 47° between both the types of grains. High-strain-concentrated regions on the surface layer of the billet were induced by the heterogeneously distributed Fe particles formed in the twin-roller casting process. The presence of these regions accelerates the abnormal grain growth in the following annealing process of the billet.